QishenYiqi dripping pill protects against myocardial ischemia/reperfusion injury via suppressing excessive autophagy and NLRP3 inflammasome based on network pharmacology and experimental pharmacology - Li, Meng; Wang, Yueyao; Qi, Zhongwen; Yuan, Zhuo; Lv, Shichao; Zheng, Yawei; Yan, Zhipeng; Wang, Mingyang; Fu, Huanjie; Fan, Xinbiao; Ji, Nan; Liu, Ming; et al. (Frontiers in Pharmacology, 2022)
Background: Myocardial ischemia/reperfusion (I/R) injury is associated with multiple serious clinical manifestations. Autophagy is upregulated in a short period of ischemia and further enhanced during reperfusion phase, which was considered as a “double-edged sword” in the pathological process of myocardial I/R injury. In addition, NLRP3 inflammasome triggers myocardial inflammatory response, which leads to cardiomyocyte death via pyroptosis and promotes subsequent myocardial remodelling. Qishen Yiqi Dripping Pill (QSYQ) has been recognized as a potential protective agent of cardiovascular diseases. Objective: We predicted the bioactive compounds, targets and pathways of OSYQ intervening on myocardial I/R injury by network pharmacology. Furthermore, we investigated the effect of QSYQ on myocardial I/R injury and explored its underlying mechanism via autophagy and NLRP3 Inflammasome. Methods: Bioactive compounds, targets of QSYQ and relevant targets of myocardial I/R injury were collected from public databases. The protein-protein interaction network, Gene ontology and KEGG pathway enrichment analysis were carried out to screen the key compounds, target genes, functional annotation and pivotal pathways. Molecular docking was used to validate the binding association between target genes and key bioactive ingredients. Furthermore, sixty SD rats were randomized into four groups: 1) sham, 2) model, 3) captopril and 4) QSYQ pretreatment (14 days before and after surgery). Each arm was subjected to ischemia/reperfusion surgery except sham arm (30 min coronary ligation, then reperfusion). Left ventricular (LV) function were evaluated and the hearts were used to evaluate size of myocardial infarction, cardiomyocyte fibrosis, and myocardial autophagosomes. Results: The network pharmacology revealed the mechanism of QSYQ intervening on myocardial I/R injury might be related to NOD-like receptor signaling pathway, PI3K-Akt signaling pathway, autophagy-animal, etc., Molecular-docking suggested the core target proteins had good binding association with bioactive compounds of QSYQ. The experiment confirmed that QSYQ attenuated myocardial infarct size, decreased inflammatory infiltration and collagen fiber deposition and alleviated the autophagosome and myocardium ultrastructure injury, leading to LV systolic function improvement. The possible mechanism of cardioprotection was due to regulating autophagy-related proteins, activating PI3K/Akt-mTOR signaling pathway, and inhibiting activation and assembly of NLRP3 inflammasome. Conclusion: QSYQ ameliorated myocardial I/R injury via suppressing excessive autophagy and NLRP3 Inflammasome.